Some limit theorems for sums of the random variables defined on a Markov process with discrete parameter - Aleškevičius, G. J. (Lithuanian Mathematical Journal, 1966)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Г. Ю. Алешкявичюс. Некоторые предельные теоремы для сумм случайных величин, заданных на однородной регулярной цепи МарковаG. J. Aleškevičius. Atsitiktinių, dydžių, apibrėžtų Markovo grandinėje, sumų ribinių teoremų klausimu